Онтоморфогенез Chamaecytisus albus (Hacq.) Rothm. (Fabaceae) і стан його локальної популяції в урочищі Чапля (Національний природний парк "Подільські Товтри") - Любінська, Л.Г.; Шевера, М.В. (Український ботанічний журнал, 2013)
Представлены результаты исследования состояния локальной популяции Chamaecytisus albus (Hacq.) Rothm. (Fabaceae) в урочище Чапля (Национальный природный парк «Подольськие Толтры», Украина). Впервые описаны онтоморфогенез, определены онтогенетические состояния вида (в частности, наличие клонов и отдельных парциальных особей), а также онтогенетическая структура (популяция характеризуется полночленным составом и левосторонним спектром). The results of studies of the state of a local population of Chamaecytisus albus (Hacq.) Rothm. (Fabaceae) of the Chaplya reservate (Podilsky Tovtry National Nature Park, Ukraine) are presented. Ontomorphogenesis of the species is described. The ontogenetic states of the species (especially clones and single partial individuals) and ontogenetic structure (the population is characterized by full — member composition and left-sided age spectra) are determined.